Piezosurgery in hemifacial microsomia: a promising exemption from conventional peri-osteotomy suffering - Wang, Xuetong; Kim, Byeong Seop; Zhang, Ziwei; Wang, Hayson Chenyu; Zhang, Yan; Chai, Gang (Frontiers in Pediatrics, 2023)
Mandibular distraction osteogenesis, a recommended therapy for hemifacial microsomia, has brought much agony because of its traumatic procedures and peri-osteotomy complications. Our study aims to retrospectively compare piezoelectric osteotome with conventional reciprocal bone saw for hemifacial microsomia patients and validate its meliority in operability, surgical risks and patient outcomes.All patients included underwent osteotomies conducted by either piezosurgery or bone saw.Information of intraoperative blood loss, operation duration, postoperative pain and complications was collected from patient files, ward round inspections and follow-ups. Among all 40 patients, 13 underwent piezo-osteotomy. Piezosurgery performed better than conventional reciprocal bone saw in decreasing intraoperative blood loss (p<0.001) and operation duration (p=0.030). No significant difference was found in hospitalization duration, total expenses or complication rates between two groups. There were positive relations between operation duration and intraoperative blood loss (p=0.042), and between hospitalization duration and total expenses (p=0.0096). Postoperative pain scores of both groups declined over time while the piezosurgery group had a statistically significant tendency (p=0.006) to suffer less than the conventional group.Piezosurgery diminishes intraoperative blood loss, operative duration, and postoperative pain, making an alternative to conventional osteotomes to mitigate patients' and families' peri-osteotomy sufferings, and a more humane solution to HFM.